Surrogate molecular markers for IGHV mutational status in chronic lymphocytic leukemia for predicting time to first treatment. Issue 8 (August 2015) - Morabito, Fortunato; Cutrona, Giovanna; Mosca, Laura; D'Anca, Marianna; Matis, Serena; Gentile, Massimo; Vigna, Ernesto; Colombo, Monica; Recchia, Anna Grazia; Bossio, Sabrina; De Stefano, Laura; Maura, Francesco; et al.
Highlights: Novel surrogate markers for ZAP-70 expression in CLL are proposed. Gene expression profiling identified genes with fold-change in expression ≥ZAP-70. Supervised analysis of these gene and IGHV mutation status was performed. CRY1 and MBOAT1 may surrogate the predictive value of IGHV mutational status. Abstract: ZAP-70 is a marker of clinical outcome in chronic lymphocytic leukemia (CLL), however its assessment suffers from a lack of standardization consensus. To identify novel markers able to surrogate IGHV mutational status, CD19(+)CD5(+)- B -lymphocytes from 216 patients enrolled in a prospective study (ClinicalTrial.gov Identifier:NCT00917540 ), underwent gene expression profiling. Samples were split into CLL-Training ( n = 102) and CLL-Validation ( n = 114) sets, and an independent supervised analysis for IGHV mutational status was performed considering all genes with gene expression equal or above that of ZAP-70. Thirty-one genes (23 up- and 8 down-regulated) and 23 genes (18 up- and 5 down-regulated) satisfied these criteria in the CLL-Training and CLL-Validation sets, respectively, and 20 common genes (15 up and 5 down) were found to be differentially regulated in both sets. Two (SNORA70F, NRIP1) of the down-regulated and 6 (SEPT10, ZNF667, TGFBR3, MBOAT1, LPL, CRY1) of the up-regulated genes were significantly associated with a reduced risk of disease progression in both sets. Forcing the afore-mentioned genes in a Cox multivariate model together with IGHV mutational status, only CRY1 (HR = 2.3, 95% CI: 1.1–4.9, P = .027) and MBOAT1 (HR = 2.1, 95% CI: 1.1–3.7, P = .018) retained their independent prognostic impact, supporting the hypothesis that these genes may potentially act as surrogates for predicting IGHV mutational status.